Lisibilité textuelle et configuration des énumérations dans un texte procédural - Beaudet, Céline (Canadian Journal of Applied Linguistics, 2002)
This article explores how configurational markers contribute to the readability of procedural texts. More specifically, it examines the role of the textual configuration of enumerations in legal writing. The author observes that enumeration is the dominant procedure in the thematisation of legislative texts, and poses her research question: In a legal text, does readability cumulate through the vertical configuration of a series of elements? Studying any type of metatextual operation from the perspective of readability involves investigating the relation between readability and textual intelligibility. The question is thus treated here by examining the language and discourse operations that interact within the text, that account for the signalling of textual organization, and that influence the clarity of the text.